Inflation Dynamics and the Great Recession - Mazumder, Sandeep (IMF Working Papers; Working Paper ;, 2011)
This paper examines inflation dynamics in the United States since 1960, with a particular focus on the Great Recession. A puzzle emerges when Phillips curves estimated over 1960-2007 are ussed to predice inflation over 2008-2010: inflation should have fallen by more than it did. We resolve this puzzle with two modifications of the Phillips curve, both suggested by theories of costly price adjustment: we measure core inflation with the median CPI inflation rate, and we allow the slope of the Phillips curve to change with the level and vairance of inflation. We then examine the hypothesis of anchored inflation expectations. We find that expectations have been fully "shock-anchored" since the 1980s, while "level anchoring" has been gradual and partial, but significant. It is not clear whether expectations are sufficiently anchored to prevent deflation over the next few years. Finally, we show that the Great Recession provides fresh evidence against the New Keynesian Phillips curve with rational expectations.